Przyczyny kryzysu finansowego z lat 2007-2008 na rynku amerykańskim - Serwach, Tomasz (Gospodarka w Praktyce i Teorii, 2011)
The 2007-2008 financial crisis is seemed to be biggest economic crisis since the Great Depression of 1929-1933. The root cause of the crisis was the collapse of subprime mortgage market. The reasons of the prior credit boom, however, are not fully understood. The main goal of the paper is to investigate the reasons of precrisis credit boom. Supply- and demand-side determinants of mortgage market are analyzed.